Peran Mediasi Kepuasan Pelanggan dalam Pengaruh Inovasi Produk dan Store Atmosphere Terhadap Loyalitas Pelanggan (Studi Kasus UMKM Gendang Jimbe kota Blitar) - Reny Puspitasari (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2023)
Customer loyalty shows behavior related to products or services for the company. Customer loyalty as a customer mindset holds a favorable attitude towards the company. This study aims to determine the effect of product innovation and store atmosphere on loyalty with customer satisfaction as a mediating variable. The population in this study were customers of jimbe drum crafts with a total sample of 100 respondents. The type of data used is primary data with data sources from the results of distributing questionnaires. Data analysis technique using path analysis. The research results show that there is a significant influence between product innovation and customer loyalty, there is a significant effect between store atmosphere and customer loyalty, and there is a significant effect between product innovation and customer satisfaction. The results of the analysis also show that there is a significant influence between store atmosphere on customer satisfaction. There is a significant influence between satisfaction on customer loyalty. Satisfaction is proven as an intervening variable in the relationship between product innovation and store atmosphere and customer .